Systematic Literature Review: Implementation of Culturally Responsive Teaching (CRT) Approach in Science Education - Choirrunisa, Choirrunisa; Maryati, Maryati (The Future of Education Journal, 2025)
Twenty first century science education demands innovation and creativity in instructional practices, along with educators’ ability to select approaches that align with students’ characteristics. Culturally Responsive Teaching (CRT) has emerged as a relevant strategy for fostering effective, inclusive, and contextual learning. This study reviews ten articles using the Systematic Literature Review (SLR) method to examine the effectiveness and optimization of CRT implementation in science learning. The literature analysis indicates that CRT not only enhances learning outcomes, interest, engagement, 21st-century skills, and critical thinking abilities, but also promotes the integration of local cultural contexts, making learning more meaningful. Implementation challenges such as limited time, insufficient understanding of students’ cultural backgrounds, and resistance to new methods require optimization strategies in the form of contextual planning, the use of interactive media, and integration with innovative learning models. These findings emphasize the need to adapt CRT-based teaching methods to meet the needs of diverse learners while providing practical recommendations for educators in its implementation.